2019
DOI: 10.1002/rhc3.12182
|View full text |Cite
|
Sign up to set email alerts
|

Leader Normativity in Crisis Management: Tales From a School Fire

Abstract: This study examines the handling of a school fire in a rural Swedish community and the role of the normalized narratives of leaders in crisis management. The article claims that leader normativity legitimizes certain positions and actions in a crisis management narrative and marginalizes others. The study uses theories on gender, boundary work and space to illuminate this claim. To explore such processes in narratives, we use feminist theory and critical management studies. The study shows that leader normativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
0
1
0
1
Order By: Relevance
“…Liderin güçlü duruşu, kriz sürecine gerçekçi yaklaşımı ve planlarını uygulamaya koyması kriz yönetimi açısından önemli görülmektedir (Alaağaçlı, 2006;Sarı ve Sarı, 2020). Kriz yönetimine yönelik alanyazında daha önceden güçlü ve tek başına karar mekanizması olarak görülen liderin krizin aşılmasında tek başına etkili olamayacağı yapılan araştırmalarda ortaya çıkmıştır (Danielsson ve Sjöstedt-Landén, 2020). Kriz yönetimi planının sağlıklı bir şekilde yürütülmesi için okul paydaşları ile krize yönelik kurulacak iletişimin önemine dikkat çekilmektedir (Badzmierowski, 2011;akt.…”
Section: Giriş Kriz Ve Kriz Yönetimiunclassified
“…Liderin güçlü duruşu, kriz sürecine gerçekçi yaklaşımı ve planlarını uygulamaya koyması kriz yönetimi açısından önemli görülmektedir (Alaağaçlı, 2006;Sarı ve Sarı, 2020). Kriz yönetimine yönelik alanyazında daha önceden güçlü ve tek başına karar mekanizması olarak görülen liderin krizin aşılmasında tek başına etkili olamayacağı yapılan araştırmalarda ortaya çıkmıştır (Danielsson ve Sjöstedt-Landén, 2020). Kriz yönetimi planının sağlıklı bir şekilde yürütülmesi için okul paydaşları ile krize yönelik kurulacak iletişimin önemine dikkat çekilmektedir (Badzmierowski, 2011;akt.…”
Section: Giriş Kriz Ve Kriz Yönetimiunclassified
“…Despite the presence of these factors, many schools suffer from poor enforcement of fire safety prevention measures (Moore and Lackney, 1993). This managerial shortcoming has led to catastrophic consequences, in many cases around the world (Danielsson and Sjöstedt-Landen, 2019). In Saudi Arabia, the statistics by the General Directorate of Civil Defense for the year 2020 (Civil Defense, 2020) indicated that a total 248 fire fighting operations were conducted on educational facilities, where the leading causes of these fires ranged from electrical circuit malfunction, pranks, open flames, misuse and handling of flammable liquids, and arson.…”
Section: Introductionmentioning
confidence: 99%